Wisdom of the crowd: evidence for density-dependent species fitness in Hyptis suaveolens (L.) Poit. - Kanhaiya Shah; Gyan Prakash Sharma (Ecological Processes)
Abstract Background Biological invasions pose severe threats to global biodiversity and human well-being. Invading populations often experience negative growth rates during the ‘lag phase’, leading to Allee effects, a density-dependent phenomenon. Allee effects reduce species fitness or plant performance due to low-density populations. The rapid spread and range expansion of an invader, Hyptis suaveolens (L.) Poit. has been reported to have negative impacts on local biodiversity in the invaded regions of the Vindhyan highlands, India. The present study examines the effects of varied population densities of H. suaveolens on its vegetative trait performance, reproductive output, and density-dependent plant population regulations. Understanding the relationship between the population density and trait modulation ability of H. suaveolens at fine and coarse scales could help strategize for management. Methods The study was conducted in invaded habitats of H. suaveolens in the Vindhyan highlands, India. Population density was divided into low-, medium-, and high-density groups. Plant performance was assessed at two scales—fine scale and coarse scale. Plant performance traits, vegetative growth, and reproductive output were estimated as plant traits (PlTs) at the fine scale and patch traits (PaTs) at the coarse scale. The plasticity response index (PI) was also estimated among three population densities. Results Results showed that PlTs-vegetative and reproductive traits, such as plant height, biomass, and number of seeds, were significantly different across densities, with medium-density individuals showing maximum plant height and plant biomass and high-density individuals exhibiting a higher number of seeds per plant. PaTs analysis revealed that plant biomass per patch was similar for medium- and high-density populations, whereas the number of seeds per patch was similar in low- and medium-density populations. PI values revealed that PlTs showed low, medium, and high plastic responses, while PaTs exhibited low and high plastic responses. Conclusions The study concludes that H. suaveolens exhibits density-dependent plant population regulations. As population density increases, low-density populations grow more rapidly, resulting in denser populations. These populations can negatively impact recipient habitats and, if left unchecked, grow into high-density populations with higher seed production. The study suggests that low-density areas should be considered a high priority for developing efficient and cost-effective management strategies. The present study emphasizes the importance of incorporating Allee effects dynamics in invasion studies for predicting high-risk/priority areas for strategizing invasive species management.